Peran Wanita Tani dalam Meningkatkan Perekonomian Keluarga (Studi Kasus Kelompok Wanita Tani (KWT) Bumi Lestari) - Sarti; Purwandari, Istiti; Listiyani (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
Nowadays, the role of women farmers is no less important in the family's economic activities. Apart from economic conditions and the status of women farmers who are also wives and mothers, many other factors make women farmers involved in family activities. This research aims to: 1) find out the role of women farmers in improving the family economy, and 2) find out the factors that influence the role of women farmers in improving the family economy. This research was carried out in Purwobinangun Village, Pakem District, Sleman Regency, Yogyakarta on February, 2024. The method used in this research was descriptive quantitative with a census method, namely using the entire existing population as the research sample. The results of this research showed that the role of women farmers in improving the family economy was high. Factors that influence the role of women farmers in improving the family economy are age and education.